Quantum Advantage in a Molecular Spintronic Engine that Harvests Thermal Fluctuation Energy. Issue 49 (31st October 2022) - Chowrira, Bhavishya; Kandpal, Lalit; Lamblin, Mathieu; Ngassam, Franck; Kouakou, Charles‐Ambroise; Zafar, Talha; Mertz, Damien; Vileno, Bertrand; Kieber, Christophe; Versini, Gilles; Gobaut, Benoit; Joly, Loïc; et al.
Abstract: Recent theory and experiments have showcased how to harness quantum mechanics to assemble heat/information engines with efficiencies that surpass the classical Carnot limit. So far, this has required atomic engines that are driven by cumbersome external electromagnetic sources. Here, using molecular spintronics, an implementation that is both electronic and autonomous is proposed. The spintronic quantum engine heuristically deploys several known quantum assets by having a chain of spin qubits formed by the paramagnetic Co center of phthalocyanine (Pc) molecules electronically interact with electron‐spin‐selecting Fe/C60 interfaces. Density functional calculations reveal that transport fluctuations across the interface can stabilize spin coherence on the Co paramagnetic centers, which host spin flip processes. Across vertical molecular nanodevices, enduring dc current generation, output power above room temperature, two quantum thermodynamical signatures of the engine's processes, and a record 89% spin polarization of current across the Fe/C60 interface are measured. It is crucially this electron spin selection that forces, through demonic feedback and control, charge current to flow against the built‐in potential barrier. Further research into spintronic quantum engines, insight into the quantum information processes within spintronic technologies, and retooling the spintronic‐based information technology chain, can help accelerate the transition to clean energy. Abstract : Molecule‐based engines with a quantum advantage are implemented using spin electronics to harvest the most basic form of energy: ambient heat. This ground‐breaking interdisciplinary approach enables electrical output above room temperature using nanoscale electrical devices. This opens quantum technologies and spintronics toward disruptive energy applications, as a possible technological game‐changer to help mitigate the energy/climate crises.